Pengaruh Budaya Organisasi dan Perilaku Kerja Inovatif Terhadap Kinerja Pegawai Sekretariat DPRD Provinsi Kalimantan Timur (Lembaga Pengembangan Kinerja Dosen, 2025)
This study analyzes the influence of organizational culture and innovative work behavior on employee performance at the Secretariat of the Regional People's Representative Council (DPRD) of East Kalimantan Province. Employee performance here is crucial to support legislative functions and public services. Using a quantitative approach with surveys and questionnaires, the data were analyzed with SPSS version 21 through multiple regression. The results show that organizational culture has a positive and significant effect on employee performance, indicating that a culture that supports collaboration and adaptability improves performance. Likewise, innovative work behavior is also proven to have a positive and significant effect on performance, indicating that initiatives and implementation of new ideas improve work quality. These findings confirm that at the Secretariat of the East Kalimantan DPRD, creating a culture that supports innovation and encourages innovative employee behavior is the key to improving performance and effectiveness of public service.